Pengaruh Faktor Intrinsik Dan Ekstrinsik Terhadap Motivasi Belajar Mahasiswa (Studi Pada Mahasiswa Jurusan Administrasi Niaga Politeknik Negeri Sriwijaya) - Heri Setiawan (MANAJEMEN INFORMATIKA, 2010)
This research done in Business Administration Department Polytechnic State of Sriwijaya and aimed at: finding the influence of intrinsic factors and extrinsic factors on student motivation to study. This research used data that collected by survey with student as respondent. One Hundred respondents were choosing as the samples by Simple Random Sampling Method. Multiple Linear Regression techniques were used to analyze data with use SPSS version 16.00 for windows. Intrinsic factors and extrinsic factors as the independent variables (X), and student motivation to study as the dependent variables (Y). The results revealed that Intrinsic factors partially has a significant effect on student motivation to study. Extrinsic factors partially has a significant effect on student motivation to study. Intrinsic factors, extrinsic factors and gender simultaneously have significant effect on student motivation to study.